Implementasi Metode Pembelajaran Peer Teaching dalam Peningkatan Keaktifan Belajar Siswa pada Mata Pelajaran Al Qur’an Hadist - Anis Fauzi; Saipul Wakit (Tarbiyatuna Kajian Pendidikan Islam, 2025)
Abstract This study aims to describe the application of the peer teaching learning method in increasing student learning activity in the subject of Al-Qur'an Hadith class VIII at MTs Negeri 10 Banyuwangi in the academic year 2024/2025. In addition, this study also aims to explain the steps of implementing the method, as well as identifying supporting and inhibiting factors in the implementation of peer teaching in the school. The type of research used is descriptive qualitative research. Data collection techniques were carried out through participatory observation, semi-structured interviews, and documentation. The research subjects consisted of Al-Qur'an Hadith subject teachers and students of class VIII at MTs Negeri 10 Banyuwangi. To maintain the validity of the data, source triangulation techniques were used. Data were analyzed through four stages, namely: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing/verification. The results of the study indicate that Al-Qur'an Hadith subject teachers have implemented the peer teaching method through three main components, namely: planning, implementation, and evaluation. In the planning stage, teachers prepare a Lesson Implementation Plan (RPP), syllabus, and media and learning aids. In the implementation stage, teachers follow the steps of the peer teaching method, where students are actively involved in teaching each other. Meanwhile, in the evaluation stage, teachers provide conclusions and assessments of the student learning process and outcomes. Supporting factors in the implementation of this method include the availability of adequate learning facilities and infrastructure and high student interest in learning, thus facilitating understanding of the material. Inhibiting factors include the physical condition of students who are tired or sleepy, lack of student confidence in expressing opinions, and time constraints that are not in accordance with the planning.